Serpentine Gallery Poetry Marathon : Saturday and Sunday 17-18 Oct. 2009 / [curators, Hans Ulrich Obrist ... et al. ; edited by Nicola Lees, Lucia Pietroiusti]. - Obrist, Hans-Ulrich; Lees, Nicola; Pietroiusti, Lucia (Koenig Books, 2011)
Published to accompany an event which took place in the closing weekend of the Serpentine Gallery Pavilion 2009, designed by Kazuyo Sejima and Ryue Nishizawa of SANAA.